Limited risks of major congenital anomalies in children of mothers with coeliac disease: a population‐based cohort study. (7th October 2014) - Ban, L; West, J; Abdul Sultan, A; Dhalwani, NN; Ludvigsson, JF; Tata, LJ
Abstract : Objective: To examine major congenital anomaly (CA) risks in children of mothers with coeliac disease (CD) compared with mothers without CD. Design: Population‐based cohort study. Setting: Linked maternal–child medical records from a large primary care database from the UK. Population: A total of 562 332 live singletons of mothers with and without CD in 1990–2013. Methods: We calculated the absolute major CA risks in children whose mothers had CD, and whether this was diagnosed or undiagnosed before childbirth. Logistic regression with a generalised estimating equation was used to estimate adjusted odds ratios (aORs) with 95% confidence intervals (95% CIs) for CAs associated with CD. Main outcome measures: Fourteen system‐specific major CA groups classified according to the European Surveillance of Congenital Anomalies and neural tube defects (NTDs). Results: Major CA risk in 1880 children of mothers with CD was 293 per 10 000 liveborn singletons, similar to the risk in those without CD (282; aOR 0.98, 95% CI 0.74–1.30). The risk was slightly higher in 971 children, whose mothers were undiagnosed (350; aOR 1.14, 95% CI 0.79–1.64), than in 909 children whose mothers were diagnosed (231; aOR 0.80, 95% CI 0.52–1.24). There was a three‐fold increase in nervous system anomalies in the children of mothers with undiagnosed CD (aOR 2.98, 95% CI 1.06–8.33, based on five exposed cases and one had an NTD), and these women were all diagnosed with CD at least 4 years after their children were born. Conclusions: There was no statistically significant increase in risk of major CAs in children of mothers with coeliac disease overall, compared with the general population.